Novel Compound C150 Inhibits Pancreatic Cancer Cell Epithelial-to-Mesenchymal Transition and Tumor Growth in Mice - Wang, Tao; Chen, Ping; Dong, Ruochen; Weir, Scott; Baltezor, Michael; Schoenen, Frank J.; Chen, Qi (Frontiers in Oncology, 2021)
Pancreatic cancer cell epithelial-to-mesenchymal transition (EMT) is an important contributor to cell invasion and tumor progression. Therefore, targeting EMT may be beneficial for pancreatic cancer treatment. The aim of the present study was to report on the inhibitory effect of the novel compound C150 on the EMT of pancreatic cancer cells. C150 was found to be cytotoxic against pancreatic cancer cells, but significantly less toxic against non-cancerous cells, with IC50 values of 1-2.5 M in multiple pancreatic cancer cell lines and >12.5 M in the non-cancerous pancreatic epithelial cell line hTERT-HPNE. C150 significantly inhibited pancreatic cancer cell migration and invasion, as demonstrated by 3-dimensional cell invasion, wound healing and Boyden chamber Transwell migration-invasion assays. Moreover, C150 treatment decreased MMP-2 gene expression in PANC-1 cells and reduced MMP-2 activity in gelatin zymography assay. In an orthotopic mouse model of pancreatic cancer, C150 significantly reduced tumor growth at the dose of 15 mg/kg by intraperitoneal injection three times per week. Furthermore, C150 enhanced protein degradation of Snail, an important EMT-promoting transcription factor, and decreased the expression of the mesenchymal marker N-cadherin, while it increased the expression of the epithelial markers zonula occludens-1 and claudin-1. The findings of the present study suggested that C150 is a novel EMT inhibitor that may be promising for inhibiting pancreatic cancer growth and metastasis.